O Alienista : eco de vozes sociais - Ito, Márcia Camargo (2006)
Based on the Line of Research, discursive process and textual production , the present work focuses on the relation between the ethos and the discourse. The ethos is revealed through the discourse, in the same way, the discourse is supported by a body and a voice . We followed the Discourse Analysis of French way, backed to the social historic lingüistic process, in the work O Alienista by Machado de Assis. In this corpus (text) we used the Maingueneau s perspective, that each ethos express a different discourse; considering the Aristotle s principle of verisimility who affirms that to the poet is not necessary to tell what happened exactly; but what could have happened. For this perspective, we analysed many fictional ethé in interaction, that results in a dialogue between many ideologies that argument with each other, promoting the text development. In this fictional world, criated by Machado de Assis, we worked with the concepts of poliphony and interdiscursivity. The presence of many voices has a functional purpose, because they are articuled strategically, to visualize the dialogue between many discourses; and, as a result, the conflit between many ideologies. If we look with attention, we will see that O Alienista projects the structure of a fictional world, reported by the narrator s ironical ethos, that denounces the society of his time, or, apart from this, the society that exists in the eternal present.